Cytogenetic analysis of multifocal breast carcinomas: detection of karyotypically unrelated clones as well as clonal similarities between tumour foci. - Teixeira, M. R. (Nature Publishing Group, 1994)
Cytogenetic analysis was performed on short-term cell cultures of two foci (A and B) from each of three multifocal breast carcinomas. In case I, four clones (three related and one unrelated) were detected in sample A. In sample B, two of the three related clones and the unrelated clone seen in A were found, as was also a third subclone showing a pattern of clonal evolution slightly different from that detected in A. In cases II and III, multiple cytogenetically unrelated clones were found in A and B, with only one clone being shared by both foci in each case. Our finding of cytogenetic similarities between macroscopically distinct tumour lesions indicates that the multifocality reflects intramammary tumour spread rather than the synchronous emergence of pathogenetically independent carcinomas within the same breast. On the other hand, the detection of karyotypic heterogeneity in the form of cytogenetically unrelated clones in all foci suggests that human breast carcinoma may be polyclonal. This polyclonality may be part of the explanation for the cellular heterogeneity commonly seen at the phenotypic level in breast cancer. IMAGES: